DIFFERENCES OF LIFE SATISFACTION AMONG ACEHNESE UNIVERSITY STUDENTS IN MALAYSIA MALE AND FEMALE - Hayati, Pelita; SIM, CHE CHEW; Fitria, Ida (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2021)
International student mobility has over the past 10-15 years become an increasingly, more students from across the world are able to participate in higher education abroad, especially those from countries with rapidly growing economies in Asian country (i.e Malaysia, Indonesia, etc). The high educational ranking of Malaysia is appealing to many Acehnese students including to study in Malaysia. Studying abroad can be a challenge having to adapt and adjust oneself to a whole new environment, culture, language, education system, lifestyle, and new friends. This study aims to investigate the levels of life satisfaction among Acehnese university students in Malaysia male and female. T-test analysis has performed to analyze the mean life satisfaction between male and female students. The result of this study reveals there was no significant difference in life satisfaction across gender. Further discussions are displayed in full view of this study.